An exploration of the experiences of and perceptions about access to antenatal care for rural women who consume alcohol during pregnancy in the Western Cape, South Africa - Mangoale, Kgahliso (Department of Public Health and Family Medicine, 2026)
Background: Globally, 2,3 billion people currently drink alcohol. South Africans have risky alcohol consumption and binge drinking patterns compared to other African countries. Western Cape rural areas have the highest prevalence of high-risk drinkers. Women's alcohol use during pregnancy has severe health and social consequences for newborns, such as Fetal Alcohol Syndrome (FAS), The prevalence of FAS in Western Cape is among the highest recorded internationally. FAS can be prevented through early interventions targeting women before and during pregnancy, through early antenatal care (ANC) providing screening, monitoring and supporting those with at-risk pregnancy. Basic ANC is freely available; however, it is only fully attended by 63,2% of pregnant women. Methods: The research explored the experiences and perceptions of rural women regarding access to ANC for women who consume alcohol during pregnancy. Face-to-face and virtual semi-structured interviews were conducted. Through purposive sampling, ten women who have experienced pregnancy and childbirth, with varying experience of drinking were recruited through a local Non-Governmental Organisation (NGO) in Stellenbosch, Western Cape, including three key informants from the NGO. Through thematic analysis, a systematic six steps process was followed to organise, analyse and identify themes from the data sets. The themes and key findings were discussed using the framework for access. Results: The experiences and perceptions of the women reflected occasional alcohol use, with six out of nine women drank alcohol during pregnancy. Women received information about the effects of alcohol during pregnancy and ANC, but most still drank alcohol. Even with limited data about reasons for continuing to drink, included relationship challenges, positive and negative treatment of health providers. Social support and module clinics as facilitators for access, physical distance and transport costs were reported as barriers to ANC access. Conclusions: The study reflected access to ANC as non-linear, the factors vary though life stages and during multiple pregnancies. Social acceptance of alcohol use and understanding of health information could relate to alcohol use during pregnancy. These factors and reasons for alcohol use during pregnancy, and interrelation to ANC access should be explored in future research. Keywords: Pregnancy; Women on farms; antenatal care; maternal alcohol use.